Reasons Behind the Failure of Students in The Computer Science Department at The University of Derna - Rabab Algadhy; Huweida Darbi; Dalya Qatish (المجلة الأفروآسيوية للبحث العلمي, 2025)
Programming skills have become increasingly important in recent years due to the rapid advances in computer science, raising the demand for programmers. However, the complexity of programming poses numerous challenges for inexperienced programmers, contributing to high dropout rates from programming courses. Individual characteristics, including unique neuropsychological traits and the lack of technological infrastructure, particularly in developing countries, are recognized as affecting the accuracy of predicting programming skills outcomes. These are major factors for consideration; hence, we investigate the high student failure rate in the Computer Science Department at the University of Derna, Libya, from the learner perspective concerning the teaching strategies employed by instructors using a qualitative data collection approach. According to the findings, the reasons behind students failure can be divided into three main categories: academic, which is represented by the challenging curriculum’s heavy reliance on logic and mathematics as well as its lack of a foundational understanding of programming and analysis; personal and psychological, which is represented by the lack of motivation, work during study sessions, stress from the material’s difficulty, and issues with time management; and administrative and environmental, which is represented by the absence of modern labs, technical equipment, and internet networks to support communication and e-learning.